(untitled) (Hematology Meeting Reports, 2009)
Background Panobinostat (LBH589) is a potent pan-deacetylase inhibitor (DACi) which has demonstrated activity in patients (pts) with CTCL in a Phase I study (Prince et al., ASCO 2007).